ULF OSCILLATIONS IN MAGMA IN THE PERIOD OF SEISMIC EVENT PREPARATION - Kopytenko Yu.A.; Nikitina L.V. (My University, 2004)
In the period of earthquake preparation, electromagnetic emissions appear over the seismic zones. In this work magma movements are considered as a possible source of ULF electromagnetic emissions over the zones with volcanic activity. Magma movements in the volcanic center are activated in the period of seismic event preparation. Hydrodynamic processes in the moving magma can lead to appearance of waves and vortices in the flow, and the electromagnetic emission induced by ULF flows in the magma is estimated.The mechanism proposed here allows us to explain some features of electromagnetic emissions in the period of the earthquake preparation: the increase of the electromagnetic emission about 1.5–2 months before an earthquake and a sharp decrease of emission about 1.5–2 days before the earthquake.
Keywords: Magma; Hydrodynamic processes; Magnetic fields